Prenatal MR Diffusion Tractography in a Fetus with Complete Corpus Callosum Agenesis - Meoded, A.; Poretti, A.; Tekes, A.; Flammang, A.; Pryde, S.; Huisman, T.A.G.M. (Neuropediatrics, 2011)
Diffusion tensor imaging (DTI) in combination with 3D-tractography reconstructions allows studying the neuro-architecture of complex brain malformations in vivo. Prenatal, in utero DTI has been limited by long acquisition times, poor signal to noise ratio and multiple artifacts. Recent developments in hard- and software allow collection of high quality DTI data sets in utero. We report on the DTI and tractography data of a fetus with a corpus callosum agenesis. Our case shows that nowadays the neuro-architecture of the fetal brain can be studied in excellent detail. Prenatal DTI and tractography may help to improve our understanding of complex brain malformations.
Keywords: corpus callosum agenesis; fetal MRI; diffusion tensor imaging